Review of physicochemical properties and analytical characterization of lignocellulosic biomass. (September 2017) - Cai, Junmeng; He, Yifeng; Yu, Xi; Banks, Scott W.; Yang, Yang; Zhang, Xingguang; Yu, Yang; Liu, Ronghou; Bridgwater, Anthony V.
Abstract: Lignocellulosic biomass is the most abundant and renewable material in the world for the production of biofuels. Using lignocellulosic biomass derived biofuels could reduce reliance on fossil fuels and contribute to climate change mitigation. A profound understanding of the physicochemical properties of lignocellulosic biomass and the analytical characterization methods for those properties is essential for the design and operation of associated biomass conversion processing facilities. The present article aims to present a comprehensive review of physicochemical properties of lignocellulosic biomass, including particle size, grindability, density, flowability, moisture sorption, thermal properties, proximate analysis properties, elemental composition, energy content and chemical composition. The corresponding characterization techniques for these properties and their recent development are also presented. This review is intended to provide the readers systematic knowledge in the physicochemical properties of lignocellulosic biomass and characterization techniques for the conversion of biomass and the application of biofuels. Graphical abstract: